Chemical variability for authenticated and commercial Artemisia absinthium L. essential oils with thujones on tephritid fruit flies: Mediterranean fruit fly Ceratitis capitata (Wiedemann) and Caribbean fruit fly Anastrepha suspensa (Loew) - Tabanca, Nurhayat; Cloonan, Kevin R.; Yang, Xiangbing; Baldemir Kılıc, Ayse; Demirci, Betul (Frontiers in Plant Science, 2025)
IntroductionFruit flies, belonging to the family Tephritidae, such as the Mediterranean fruit fly (Ceratitis capitata Wiedemann) and the Caribbean fruit fly (Anastrepha suspensa Loew), are recognized as major agricultural pests worldwide. Their larval stages infest a wide array of fruits and vegetables, causing significant economic losses through direct damage to crops and restrictions on international trade. Conventional pest management, heavily reliant on synthetic pesticides, has led to health concerns and the emergence of pesticide resistance. In response, semiochemicals, particularly essential oils and their constituents, are emerging as promising alternatives.MethodsIn this study, authenticated Artemisia absinthium L. (wormwood, Asteraceae) (Asd) essential oil (EO) was compared with five lab-distilled commercial A. absinthium EOs (A1 to A5) using gas chromatography with a flame ionization detector (GC–FID) and gas chromatography–mass spectrometry (GC–MS), and essential oils were tested in behavioral assays on sterile male C. capitata. Key components were evaluated for their potential attraction of male C. capitata, and the toxicities of compounds to female A. suspensa were determined.ResultsCluster analysis revealed three major groups of compounds: β-thujone and (Z)-β-ocimene epoxide, β-thujone and camphor, and only camphor-rich. In short-range attraction bioassays, Asd and A1 samples captured the most male C. capitata at 30 minutes. These findings were linked to a higher α,β-thujone content in samples Asd (41.04%) and A1 (29.6%). A set of bioassays were conducted to compare the response of C. capitata to α-thujone, α,β-thujone, and tea tree oil, a strong medfly attractant. Medflies were similarly attracted to both α-thujone and α,β-thujone from 30 to 90 minutes. In a subsequent bioassay, α-thujone and α,β-thujone demonstrated strong toxicity to adult female A. suspensa, with the LD50 values being 0.21 and 0.14 μg/μL, respectively.DiscussionThese findings demonstrate that thujones have both attractant properties for male C. capitata and significant toxicity to A. suspensa, making them promising candidate compounds for integration into comprehensive integrated pest management strategies.